Release studies of naked DNA, polyplexes and lipoplexes from polymeric films - Ramgopal Yamini (2008)
This report details the study done on the stability, release and transfection efficiencies of naked DNA, polyplexes and lipoplexes from different polymeric films in which they were entrapped. The polymeric system studied includes PLGA (53/47), PCL and PEVAC .The release profile was determined by quantifying the amount of DNA released at specific time points over a period of 1 month, utilizing the fluorescence of ethidium bromide.The bioactivity of the released complexes were determined by in vitro cell transfection using COS 7 cells. Transfection was observed from lipoplexes samples from both PCL and PEVAC samples on day 9. The results also demonstrated that bioactivity of the encapsulated systems were superior to the naked DNA.